2018
DOI: 10.1016/j.mib.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal drug resistance: evolution, mechanisms and impact

Abstract: Microorganisms have a remarkable capacity to evolve resistance to antimicrobial agents, threatening the efficacy of the limited arsenal of antimicrobials and becoming a dire public health crisis. This is of particular concern for fungal pathogens, which cause devastating invasive infections with treatment options limited to only three major classes of antifungal drugs. The paucity of antifungals with clinical utility is in part due to close evolutionary relationships between these eukaryotic pathogens and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
289
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(324 citation statements)
references
References 55 publications
1
289
0
9
Order By: Relevance
“…Candidemia has an incidence of between 1.1 and 24 cases per 100,000 individuals and associated high mortality rates often above 30% (Grubb et al ., ; Sanguinetti et al ., ). The worldwide emergence and spread of antifungal‐resistant strains and the availability of only a few classes of antifungal drugs further increase the difficulty of treating invasive fungal infections (Morace et al ., ; Perlin, ; Revie et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Candidemia has an incidence of between 1.1 and 24 cases per 100,000 individuals and associated high mortality rates often above 30% (Grubb et al ., ; Sanguinetti et al ., ). The worldwide emergence and spread of antifungal‐resistant strains and the availability of only a few classes of antifungal drugs further increase the difficulty of treating invasive fungal infections (Morace et al ., ; Perlin, ; Revie et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Epidemiology studies have shown that drug‐resistant Aspergillus and non‐ Aspergillus molds are commonly observed among those with breakthrough infections . Prolonged exposure to suboptimal voriconazole concentrations may mechanistically promote acquired resistance and selection of subpopulations with primary resistance . The CYP2C19*17 allele is a risk factor for low voriconazole concentrations and can affect ~ 25% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Prolonged exposure to suboptimal voriconazole concentrations may mechanistically promote acquired resistance and selection of subpopulations with primary resistance. [23][24][25] The CYP2C19*17 allele is a risk factor for low voriconazole concentrations and can affect ~ 25% of patients. There is limited clinical guidance for utilization of prophylactic voriconazole in CYP2C19 rapid metabolizers, but Clinical Pharmacogenetic Implementation Consortium guidelines have recommended avoidance of voriconazole for CYP2C19 rapid metabolizers with an invasive fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the ecology of pathogenic yeasts is critical to human health for multiple reasons. First, mortality from infections by these yeasts remains high, and candidiasis is the fourth most common hospital-associated bloodstream infection (4, 14, 15). Second, Candida auris recently emerged as a multi-drug resistant opportunistic pathogen, with additional strains exhibiting resistance to many anti-fungal drugs (14, 16).…”
Section: Observationmentioning
confidence: 99%
“…First, mortality from infections by these yeasts remains high, and candidiasis is the fourth most common hospital-associated bloodstream infection (4, 14, 15). Second, Candida auris recently emerged as a multi-drug resistant opportunistic pathogen, with additional strains exhibiting resistance to many anti-fungal drugs (14, 16). Finally, it is unclear whether there might be environmental reservoirs that could act as contact points for their primary hosts, or whether the niches of pathogenic yeasts are indeed exclusively endothermic animals and clinical environments (17).…”
Section: Observationmentioning
confidence: 99%